The Influence of CSR, Profitability, and CAR on Company Value (Case Study: Conventional Commercial Banks Listed on the IDX 2021–2024) - Wardani, Monica Kusuma; Lisiantara, Gregorius Anggana (Manunggal Halim Jaya, 2026)
Examining the effects of CSR, profitability as measured by ROA, and CAR on company value in traditional commercial banks listed on the IDX for the years 2021–2024 is the aim of this research. The whole population of traditional commercial banks that were listed on the IDX between 2021 and 2024 is used in this analysis. This research uses secondary data analysis and a quantitative methodology. Purposive sampling with a number of well chosen criteria is the sampling method used, yielding a sample of 80 banks. Data was processed using Eviews 13 and using descriptive statistical analysis. Multiple linear regression analysis is the method of data analysis that is used. According to the study's findings, ROA significantly and favourably af ects business value, but CSR and CAR have no influence.